Alien species alert: Crassostrea gigas (Pacific oyster) - Miossec, Laurence; Le Deuff, Rose-marie; Goulletquer, Philippe (ICES, 2009)
The Pacific oyster (Crassostrea gigas, Thunberg, 1793) is one of 20 species in the genus Crassostrea. Although native to the Japan/Korea region, C. gigas is a hardy species that has been introduced to a number of countries worldwide, including the US, Canada, the UK, France, Korea, China, New Zealand, Australia, South Africa, and South America, mainly for aquaculture purposes (Mann et al., 1991; Orensanz et al., 2002). As a result, C. gigas has become the leading species in world shellfish culture, with an estimated production of 4.6 million t in 2006 (FAO, 2008). Because C. gigas does not require additional food to sustain its growth, this species is relatively inexpensive and easy to produce. Its capacity to adapt to various environmental conditions and temperature fluctuations, coupled with its rapid growth and resistance to highly turbid areas, contributes to its success.